Sea change - Viva, Frank (TOON Books, 2016)
"Follows a young boy who is reluctantly sent to spend the summer in a remote part of Nova Scotia. As the summer wears on, the hero forges solid friendships with other kids in the small fishing community and is changed forever by the experience"--